2012
DOI: 10.1088/1367-2630/14/8/083035
|View full text |Cite
|
Sign up to set email alerts
|

A three-dimensional silicon photonic crystal nanocavity with enhanced emission from embedded germanium islands

Abstract: We report the realization of a silicon three-dimensional photonic crystal nanocavity containing self-assembled germanium-island emitters. The three-dimensional woodpile photonic crystal was assembled layer by layer by micromanipulation using silicon plates grown by molecular beam epitaxy. An optical nanocavity was formed in the center of the photonic crystal by introducing a point defect into one of the plates. Measurements of the filtered spontaneous emission from the Ge islands in the active plate through th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 29 publications
2
23
0
Order By: Relevance
“…This conclusion is confirmed by Ref. [117], where it was reported that the Ge islands have a substantial non-radiative recombination rate γ nrad .…”
Section: Emission In a Nanobox For Lightsupporting
confidence: 74%
See 1 more Smart Citation
“…This conclusion is confirmed by Ref. [117], where it was reported that the Ge islands have a substantial non-radiative recombination rate γ nrad .…”
Section: Emission In a Nanobox For Lightsupporting
confidence: 74%
“…Emission in a 3D photonic bandgap cavity has also been studied by the Tokyo group [99,100,117]. In the first study, a layer of InAsSb quantum dots was embedded in the central layer where the cavity was located [99].…”
Section: Emission In a Nanobox For Lightmentioning
confidence: 99%
“…Embedding of Ge QDs in a photonic crystal slab (PCS) or resonator (PCR) for emission enhancement in the 1.3–1.5 μm telecommunication range has recently been demonstrated. 23 25 For the efficient coupling of QD emission to PCS or PCR modes, the precise position of the dot relative to the two-dimensional mode pattern of the respective photonic crystal (PC) structure is crucial. Nevertheless, most efforts in the group-IV system up to now were based on randomly nucleated Ge QDs without any control of the dot position.…”
mentioning
confidence: 99%
“…Nevertheless, most efforts in the group-IV system up to now were based on randomly nucleated Ge QDs without any control of the dot position. 23 25 Efficient coupling to PCR modes is particularly important in the case of single-dot emitters for quantum optical applications, where source implementations in the III–V system are commonly based on the fabrication of a dedicated PCR around a singled-out randomly nucleated QD. 26 In contrast to the III–V system, where uniform site-controlled growth of single QDs remains challenging, 27 29 a robust technological basis for precise positioning of size-homogeneous Ge QDs on pit-patterned substrates has recently been established.…”
mentioning
confidence: 99%
“…The well‐known drawbacks of SiGe QDs as light emitters are the indirect band gap of Si and Ge and the weak electron binding. Improvements of the optical properties of SiGe QDs, for example, with respect to emission linewidth and intensity, were proposed and demonstrated by the use of site‐controlled QDs, QDs embedded in strained layers, or resonators such as photonic crystal cavities (PhC) or microdisks . Recently, we demonstrated that introducing single defects by the implantation of heavy ions into the QDs can overcome the indirect nature of their radiative transitions, leading to optically pumped lasing from microdisk cavities containing such defect‐enhanced quantum dots (DEQDs) as gain material.…”
Section: Introductionmentioning
confidence: 99%